Visión criminológica del delito online grooming = Criminological viewof Online Grooming - Sobrino, Alberto Bragado (Behavior & Law Journal, 2020)
The scientific literature identifies three types of individuals who perpetrate online grooming: hypersexualized, adaptive and intimate. The present study aims to explore the profile of the potential offender who perpetrates this crime and their different typologies. To this end, a joint sample of 258 grooming cases was compared. On the one hand, 243 are cases of online grooming in the United States. On the other hand, 15 are cases of online grooming in Spain. The results indicate that online grooming is mainly perpetrated by a man between twenty-one and thirty years old, sexually or emotionally motivated. The effect of the prolongation of the time between contact and the sexual proposition in relation to the strategies used by the aggressors reflects the different types of groomers found in this phenomenon: intimate, adaptive and hypersexualized.